2016
DOI: 10.1007/s00436-016-5317-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and morphological descriptions of Ceratomyxa collarae n. sp. and Ceratomyxa leucosternoni n. sp. from marine ornamental fishes of Indian waters

Abstract: Two novel species of Ceratomyxa infecting marine ornamental fishes from Indian waters are described. Marine ornamentals, Chaetodon collare and Chaetodon decussatus, collected from Vizhinjam, along the southwest coast of India and Acanthurus leucosternon collected from Lakshadweep islands of Arabian Sea revealed Ceratomyxa infections in their gall bladders. Mature spores of Ceratomyxa from Chaetodon collare and Chaetodon decussatus were elongate and slightly crescentic, with rounded ends, and measured 5.20 ± 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The intraspecific threshold values used for clinid ceratomyxids in present study are higher than commonly reported in other myxozoan clades [ 17 ] but they have been carefully evaluated with regard to the fast evolution of the studied molecular markers in this long-branched parasite group and we recommend using these cut-offs for this specific group of ceratomyxids in future studies. For example, relatively low values of maximum SSU rDNA intraspecific divergences were reported for ceratomyxids from Indian (up to 0.8%) [ 81 ], Australian (up to 1.3%) [ 26 , 27 , 30 ] and North Atlantic fishes (up to 1.6%) [ 46 ], whereas wide ranges up to 7% in C . cottoidii were encountered for South African clinid ceratomyxids (present study).…”
Section: Discussionmentioning
confidence: 99%
“…The intraspecific threshold values used for clinid ceratomyxids in present study are higher than commonly reported in other myxozoan clades [ 17 ] but they have been carefully evaluated with regard to the fast evolution of the studied molecular markers in this long-branched parasite group and we recommend using these cut-offs for this specific group of ceratomyxids in future studies. For example, relatively low values of maximum SSU rDNA intraspecific divergences were reported for ceratomyxids from Indian (up to 0.8%) [ 81 ], Australian (up to 1.3%) [ 26 , 27 , 30 ] and North Atlantic fishes (up to 1.6%) [ 46 ], whereas wide ranges up to 7% in C . cottoidii were encountered for South African clinid ceratomyxids (present study).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular characteristics, such as sequence similarity and variable sites, are usually regarded as important evidence for species identification and discrimination of closely related myxosporean species (Liu et al, 2019; Sanil et al, 2017; Zhao et al, 2013). Generalizing, when the similarity of the two sequences is less than 96.4% (Atkinson et al, 2015; Ferguson et al, 2008) or variable sites of intra‐species identification are more than ten (Zhao et al, 2013), it can be considered to be different species.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, species identification of myxosporeans was based on myxospore morphology. However, morphological variation of myxospores within a species, or morphological similarities between species create challenges for myxosporean species identification (Ferguson et al, 2008; Liu et al, 2011; Sanil et al, 2017; Thabet et al, 2016; Whipps & Kent, 2006; Zhai et al, 2016). As such, DNA sequence data has become indispensable for investigating the taxonomy and systematics of myxosporeans.…”
mentioning
confidence: 99%
“…This diversity coupled with the plasticity of myxospore morphology of Ceratomyxa causes challenges for species identification. It is thus recommended to incorporate molecular data in species classification [14,15]. Currently, novel species are described using characters that include myxospore morphology, small subunit (SSU) rRNA gene sequences, and information of host species, infection site (tissue tropism), and geographic locality.…”
Section: Introductionmentioning
confidence: 99%